Unit roots: Identification and testing in micro panels - Stephen Bond; Céline Nauges; Frank Windmeijer (Centre for Microdata Methods and Practice (cemmap), 2005)
We consider a number of unit root tests for micro panels where the number of individuals is typically large, but the number of time periods is often very small. As we discuss, the presence of a unit root is closely related to the identification of parameters of interest in this context. Calculations of asymptotic local power and Monte Carlo evidence indicate that two simple t-tests based on ordinary least squares estimators perform particularly well.
Keywords: C12; C23; 330; Generalised Method of Moments; Identification; Unit Root Tests